Coastal Armoring Impacts on Beaches and Sea Turtles - Martha Monroe; Ray Carthy; Melissa Hill (EDIS)
Close to 19.6 million people live in Florida, and 76.5% of them, or approximately 15 million, live on the coast. Florida’s coasts are attractive despite the increasing risks from sea-level rise and more frequent climatic events such as hurricanes and coastal flooding. At particular risk from these erosive events are Florida’s 825 miles of sandy beaches. Coastal armoring is a physical barrier placed with the intent of protecting structures from storm, surf, and erosion damage. This publication explains how coastal armoring works and the impacts it has on nearby beaches and sea turtle habitat.